Knowledge and Roles of Non Governmental Organizations (NGOs) in Climate Change Mitigation and Adaptation in Anambra State - J C Iwuchukwu; O. J Nwankwo; O. I Ogbonna (Journal of Agricultural Extension, 2014)
The study ascertained knowledge and perceived roles of state based-Non Governmental Organizations (NGOs) in climate change mitigation and adaptation in Anambra State, Nigeria. Multistage random sampling technique was employed to select thirty five respondents from 4 local government areas and 7 NGOs in the state while data were collected with questionnaire. Percentage and mean scores were used in analyzing the data. Results revealed that greater proportion (60%) of NGO members were not aware of climate change while about 63% indicated that issues on climate change have not been included in their programme. They perceived major causes of climate change as over industrialization (M=2.77) and use of automobiles (M=2.74) while land degradation and over flooding (M=2.77 each) were major effects of climate change. Proper land use and management (M=2.89) and reforestation/ (M=2.83) were mitigation measures while minimum tillage (M=2.74) and use of resistant varieties (M=) were adaptive measures to climate change as perceived by them. They further perceived creation of awareness and sensitization of rural people/farmers about climate change (77.1%each) and helping government in enforcement of policies and laws that will help to mitigate climate change (57.1%) as roles they can play in climate change mitigation and adaptation. They did not perceive any major problem that can mar their contributions to climate change issue. The study emphasized on the need for private sector especially NGOs investment and participation in global and sensitive issues like climate change. This will go a long way in discovering and disseminating quick and useful information on climate change and probably ultimate solution to it.